Analisis Perbandingan Beban Operasional dan Pendapatan Operasional (BOPO) pada PT Bank Muamalat Indonesia Tbk. Cabang Batam - Fatimah Eka Ningsih (Politeknik Negeri Batam, 2013)
The operational efficiency carried out by the bank in order to determine whether the operations related to the core business of the bank, done properly (in accordance with the expectations of management and shareholders) and is used to indicate whether the bank has to use all the factors of production with appropriate and successful order . The operating efficiency of a bank that is projected to BOPO affect the performance of the bank. The lower the ratio of ROA, the more efficient the bank in its operations and then vice versa